2020
DOI: 10.1007/s10750-020-04257-3
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in midge assemblages (Diptera Chironomidae) in an alpine lake from the Italian Western Alps: the role and importance of fish introduction

Abstract: Introduction of exotic species is one of the major human impacts for decline in autochthonous biodiversity. In freshwater lentic environments, alien fish introduction heavily shapes macrobenthic invertebrate structure, with special regard for Chironomidae (Diptera) community. These effects could be more evident in alpine lakes whose environments are considered as remote and undisturbed, but extremely susceptible and vulnerable to both natural and anthropogenic impacts. In this context, modern and subfossil chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…they converted dietary precursors to EPA intrinsically). Based on δ 13 C EPA values, ‘lake spiders' obtained their EPA from Chironomidae, one of the most abundant emergent aquatic insect taxa found in lakes (Armitage 1995, Martin‐Creuzburg et al 2017, Selene et al 2020, Mathieu‐Resuge et al 2020), making them a likely food source for ‘lake spiders'. Because the δ 13 C EPA values of emergent aquatic insects overlapped with those from terrestrial insects, it was not possible to trace the origin of spider EPA using δ 13 C EPA values alone.…”
Section: Discussionmentioning
confidence: 99%
“…they converted dietary precursors to EPA intrinsically). Based on δ 13 C EPA values, ‘lake spiders' obtained their EPA from Chironomidae, one of the most abundant emergent aquatic insect taxa found in lakes (Armitage 1995, Martin‐Creuzburg et al 2017, Selene et al 2020, Mathieu‐Resuge et al 2020), making them a likely food source for ‘lake spiders'. Because the δ 13 C EPA values of emergent aquatic insects overlapped with those from terrestrial insects, it was not possible to trace the origin of spider EPA using δ 13 C EPA values alone.…”
Section: Discussionmentioning
confidence: 99%
“…This makes mountain lakes important sentinels for indirect pressures due to global change [18]. In turn, dramatic consequences for these ecosystems can arise through direct pressures, such as cattle herding [19], hut construction [20], and tourism [21], which often lead to the eutrophication of mountain lakes, while fish stocking disturbs their food webs and internal nutrient recycling [22][23][24][25][26]. These direct pressures may be amplified by climate change [20,[27][28][29][30], which is particularly pronounced in mountain regions such as the European Alps [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Various other levels in the food web including chironomids and algae (diatoms) have also been used to infer change in fish communities. Chironomids are typically the dominant benthic macroinvertebrates in lakes and the composition of chironomid assemblages changes in response to fish introductions due to predation (Raposeiro et al ., 2017; Selene et al ., 2020) and through other ecosystem shifts (Uutala, 1990). In an example of an indirect ecosystem shift, Uutala (1990) found that the abundance of predatory chironomid larvae increased in response to higher prey abundance (i.e.…”
Section: Methods For Measuring the Impact Of Disturbance On Native Fr...mentioning
confidence: 99%